Complexity leadership in action: a team science case study - Jiang, Gemma; Boghrat, Diane; Grabmeier, Jenny; Cross, Jennifer E. (Frontiers in Research Metrics and Analytics, 2023)
This team science case study presents a successful application of complexity leadership theory to redesigning a cross-disciplinary science institute's weekly research coordination meeting. The narrative arc of this paper follows four stages of the adaptive process in complex adaptive systems: disequilibrium, amplification, emergence, and new order. Building on insights from this novel application of complexity leadership theory, we share important implications for team science practice pertaining to generating momentum for change, re-examining power dynamics, defining critical teaming professional roles, building multiple pathways towards team capacity development, and holding adaptive spaces. Promising areas for further exploration are also presented.